Prospective Validation of a Transcriptomic Metric in Severe Trauma. Issue 5 (May 2020) - Raymond, Steven L.; Hawkins, Russell B.; Wang, Zhongkai; Mira, Juan C.; Stortz, Julie A.; Han, Feifei; Lanz, Jennifer D.; Hennessy, Laura V.; Brumback, Babette A.; Baker, Henry V.; Efron, Philip A.; Brakenridge, Scott C.; et al.
Abstract : Supplemental Digital Content is available in the text